Balancing a heavy workload in a BPO company to satisfy both client and employee needs - Parana, Mark Angelo B. (Animo Repository, 2017)
The declining quality of work output and increasing employee turnover of my team in IBM have been noticed by our client and became a problem of the management. A problem which should be addressed to maintain client satisfaction and continued business partnership. Our high turnover rate somehow connotes our inability to maintain good people and develop subject matter experts. It is part of our client's strategy for continuous growth to keep the best talent in the market. Then, it is important for us to have a roster of very knowledgeable resources that would keep our clients processes rolling smoothly and maintain stability as well as to help our client fulfill their mission. But with the rate of our tenure members leaving and new employees coming in as their backfill, the scale of focus in our team is often gearing towards transitions and training which compromises our teams output. This had lead to our client's primary concern which is our declining work quality. Thus, our local management team initiated an intensive review on my team and on each individual. In line with clients point of view, there's a possibility of correlation between people leaving our team and the decline in our work quality. But it was unfounded to say that the former is the real reason why we have the latter. Both could've been driven by exactly the same thing. Measuring employee turnover can be helpful to us to examine employees reasons for leaving the company - or estimate the cost-to-hire for budget purposes which is also an important factor to our client. In terms of work quality, it differs depending on the type of work. It may be on services, goods or other else. Most often, it refers to the perfection of the work, regardless of what type. But, if quality is defined as the absence of defects or mistakes, we indirectly encourage employees to cover up mistakes or problems quickly, without drawing attention to them (Item 9: Doing Quality Work, 1999). Thus, employees are not driven to provide good quality of their work. It brought the idea that we might not be going to address the real problem but just the symptom of it. This action research project sought to find the solution to better address our clients concern about the decline in work quality and employee turnover which goes hand-in-hand. We begun by analyzing the basic part of the formula - i.e. our team members. Going deeper into the situation with thorough observation, data gathering, and interacting with people, we were able to understand what's been happening. The declining work quality is just a symptom of a different issue which has been branching out to other problems. People leaving our team was somehow a result of it as well. In the first cycle, this action research addressed the teams problem about heavy workload which tends to be the most common concerns from the team. and was manifested with high overtimes, high process errors and at worst is attrition. The research used the action research cycle by Coghlan and Brannick following the 4 dimensions of construction, planning the action, taking the action and evaluating the taken action. The first cycle encompasses three distinct phases which are needed to balance the heavy workload. These were the hiring phase, training phase and workload redistribution phase. After evaluating the result, it was realized there's a problem with the training phase which hinders us to proceed to the end goal immediately. Thus, the second cycle addresses the need for improvement of the training plans we had as it lacks the focus on the communications aspect our teams role. After taking all the actions, me and my whole team were still able to realize our objectives.